Blockchain technology in e-Healthcare management - Namasudra, Suyel; Albuquerque, Victor Hugo C. de (Healthcare technologies series, 2022)
The healthcare arena has seen a shift in recent years, with more healthcare provisions being delivered or managed via electronic means. Healthcare providers can now provide patients with diagnosis, treatment, monitoring, or a prescription without ever sharing the same physical space. With so much more patient data now stored and accessed electronically, the security of this information is ever more critical to the delivery of effective and efficient healthcare services. As blockchains are resistant to modification of their data, blockchain technology therefore provides traceable and reliable security to e-Healthcare systems and services. Introducing the fundamentals of blockchain technology and discussing its applications in the e-Healthcare sphere, the editors highlight recent research and development in blockchain technology, specifically in healthcare environments such as e-healthcare records and data security, health insurance management and fraud detection, pharmaceutical supply chain management and drug traceability, and IoT enabled patient monitoring. Including a case study on managing e-Healthcare data the editors also explore the challenges and future directions of using blockchain technology in delivering and managing e-Healthcare provision. Written by a range of international experts, the book will be of interest to researchers and academics in information security, data scientists, and healthcare professionals/administrators with responsibility for e-Healthcare records.